Teaching chunks of language: um trabalho com o seriado Gilmore Girls em aulas de inglês como língua estrangeira - Ramalho, Mainly Reinhardt Vieira dos Santos (2011)
This paper aims to study the usage of American TV series in English as a foreign language classes through the gathering of chunks of language. Though we start this dissertation from the description of the communicative and its innovative principles by presenting the communicative competence and its four divisions strategic, grammatical, discursive and sociolinguistic based on researches like Hymes (1972), Brown (2000), Richards (2006), Richards e Roberts (1986) and Savignon (1983; 1991). Besides we describe the importance of the realia in a communicative class. As well as we discuss the lesson of the communicative approach and the four abilities reading, writing, speaking and listening. Still talking about the communicative lesson we discuss about teaching grammar, vocabulary and culture. The choice of using TV series is justified because they are a rich source both linguistic and cultural of the English language (North American) and we can find a plenty of examples chunks of language, collocations, phrasal verbs, and idioms. In our analysis we gathered not only the linguistics but also the cultural references of the first episode of Gilmore Girls by using software known as Unitex® that searches the chunks in the script selected and finally we propose some activities based on the analysis.